DAC is dead? Implications for teaching development studies. (15th July 2018) - Kilby, Patrick
Abstract : This paper argues that the Western paradigm of foreign aid promoted by the Development Assistance Committee is rapidly losing relevance in development studies and its related academic teaching programmes. The longstanding Southern‐led approaches to aid and development are now coming to the fore. China's Five Principles of Peaceful Coexistence (finalised at Bandung in 1955) and the Eight Principles for Economic Aid and Technical Assistance to Other Countries (1964) are increasingly emphasised as points of difference to Western aid. It is the rise of the South that has challenged the dominant development paradigm(s) over the past 50 years. The discipline of development studies has been slow to address these challenges in how it trains future development practitioners. I will argue that development studies programmes in Australian universities have a focus on Western foreign aid: either questioning its hegemonic nature as a tool for neo‐liberal or neo‐colonial development on the one hand; or questioning aid effectiveness and how well it addresses contemporary challenges. This paper explores the challenges in examining South–South cooperation and a different development paradigm in producing relevant development studies curricula and pedagogies.